A novel vector for magnetic resonance imaging-guided chemo-photothermal therapy for cancer - Kong, Ji chuan; Li, Yang; Ma, Wang; Du, Yu rong; Liu, Lei; Qu, Tian tian; Liu, Shuo shuo; Wang, Meng li; Dou, Wei (Frontiers in Oncology, 2022)
As an effective strategy for oncotherapy, developing efficacious drug delivery systems for cancer combination therapy remains a major challenge. To improve nanodrug biocompatibility and composite function facilitating their clinical conversion application, a novel nanocarrier was presented by a facile method through conjugating humic acid with gadolinium ions to synthesize HA-Gd with good biocompatibility and dispersity. HA-Gd exhibited high photothermal conversion efficiency up to 38%, excellent photothermal stability, and high doxorubicin (DOX) loading capacity (93%) with pH-responsive release properties. HA-Gd loading DOX showed a combined chemo-photothermal inhibitory effect on tumor cells. Compared with lipid-DOX, HA-Gd-DOX had a more significant inhibitory effect on tumor growth and fewer side effects. T1-weighted MRI contrast toward tumor tissue provided HA-Gd with an MRI-based cancer diagnosis. This study revealed the great potential of humic acids as a novel vector for developing more drug carriers with desirable functions for clinical anticancer therapy.